Biocompatibilidade da terapia fotodinâmica: estudo in vitro e in vivo - Santos, Ludmilla Mota da Silva [UNESP] (2014)
Introduction: Photodynamic therapy (PDT) is based on a set of biological, physical and chemical processes that occurs through the activation of a photosensitizer (PS) with light (laser or LED) to destroy target cells. The aim of this study was to evaluate the cytotoxicity and tissue response of PDT including the production of cytokines (IL - 1β and IL - 6). Methods: 1) For the cytotoxicity test groups were divided into: 5% sodium hypochlorite; 2.5% sodium hypochlorite; 2% chlorhexidine; saline; PDT (curcumin + Led blue light); and control (culture medium). The solutions were diluted in DMEM culture medium (1x104 cells) and placed in 24 -well plates with mouse fibroblast line (L929). After 6, 24 and 48 hours, the MTT assay was used to assess cell viability and ELISA assay was used to assess cytokine in the supernatant. 2) To test the tissue response, the groups were divided into: control (saline); 2.5%; sodium hypochlorite, 5% sodium hypochlorite; 2% chlorhexidine; TFD (curcumin + Led blue light). The solutions were placed into polyethylene tubes and implanted in the dorsal tissue of Wistar rats for 7, 15, 30, 60, and 90 days. The tubes were removed with surrounding tissue and divided in half and one half was stained with hematoxylin and eosin and the other half used to assess cytokine by ELISA. Statistical analysis was performed using ANOVA, Kruskal Wallis or Tukey test (p < 0.05). Results: For the in vitro study, PDT and saline showed low cytotoxicity similar to the control group (p > 0.05) , less than sodium hypochlorite (2.5% and 5%) and 2% chlorhexidine (p < 0.05) at all time periods. All solutions released cytokines similar to control (p > 0.05) amount. As for the in vivo study, all solutions caused severe inflammatory reaction after 7 days, which decreased with time. No inflammation was observed at 90 days in the PDT group similar to the control (p > 0.05) . All materials...